Perceived Stress and Sources of Stress Among Medical Undergraduates of Fatima Jinnah Medical University, Lahore, Pakistan (Medical Forum Monthly, 2024)
ABSTRACTObjective: To find out level of perceived stress and the probable stressors.Study Design: Observational / descriptive / cross-sectional survey StudyPlace and Duration of Study: This study was conducted at the Department of Obse and Gynae, Fatima Jinnah Medical University, Lahore during the period of one month of March 2016.Materials and Methods: Using convenient sampling, 387 medical students completed the PSS-10 and a 30 item stress questionnaire. The data was analyzed with SPSS-22 software. ANOVA techniques were used to analyze differences in mean perceived stress score amongst different classes. Binary Logistic Regression Analysis was performed to determine core stress factors. P-Value was set at 0.05.Results: The total response rate was 99.25%(397/400). The total mean PSS was 20.84 (SD=6.44) and was significantly highest amongst 1st year students with a score of 23.54 (SD=7.04). The prevalence of academic, psychological and health related stressors were 39%, 30% and 31% respectively.Conclusion: A high level of perceived stress was noted among fresh enrolling MBBS students. Academic stressors were the most frequent stressors. It is important for medical educators to appreciate the level of stress and its various causes among medical undergraduates. So, we suggest early guidance and regular assessments of stressors which will help prepare students for stressful career of a health professional.